Knowledge and Attitude of Nigerian Dentists to Immediate Loading of Dental Implants - K.O. Obagbemiro; Y.O. Ajayi; P.A. Akeredolu; G.T. Arotiba (Nigerian Dental Association, 2020)
Background: Treatment with dental implants is an attractive option in the practice of restorative dentistry. Majority of patients treated with dental implants have reported remarkable improvement in function, esthetics and psychological status. Dental implant placement traditionally was advocated for healed extraction sites; however, the development of a better understanding of the biologic principles of bone healing has led to preferment of immediate implants. Aim: To evaluate the knowledge and attitude of Nigerian dentists to immediate loading of dental implants. Materials and Methods: Pretesting of the questionnaires was earlier carried out on 20 dentists at the Lagos University Teaching Hospital, Lagos. It was a questionnaire based cross sectional study conducted among dentists that attended Nigerian Dental Association Conference. Participants were recruited through a simple random sampling through a selection of "Yes or No". Questionnaires were given to individuals that picked the "Yes" option. Three hundred and fifty questionnaires were distributed and 250 were duly filled and returned to the researchers. Analysis of data was done using SPSS Version 20. Results: Sixty five point eight percent of the participants were females and the commonest age group of the respondents was 35-39 years (30.8%). Most of the respondents (81.8%) have a minimum of 10 years clinical experience. 74.4% of respondents had knowledge of immediate loading of dental implants however, 66.2% of respondents do not place dental implants in their clinics. 74.4% of those that do, do not practise immediate loading of dental implants. Conclusion: Though most dentists know about immediate loading of dental implants, only a few practise it.